Antibacterial Efficacy of AgNO₃ Combined with Cymbopogon citratus Extract and Chitosan Nanocomposite Against Pseudomonas aeruginosa - Azrianty, Annisa; Komariah, Komariah; Ranggaini, Monica Dewi; Anggraeni, Rezky; Halim, Johni; Nugroho, Didi (Jurusan Farmasi Universitas Negeri Gorontalo, 2025)
Infections caused by pathogenic bacteria such as Pseudomonas aeruginosa present significant challenges in clinical practice, particularly due to rising resistance to conventional antibiotics. The development of environmentally friendly, nanotechnology-based antibacterial agents is considered a promising alternative. This study aimed to evaluate the antibacterial activity of a nanocomposite comprising silver nitrate (AgNO₃), Cymbopogon citratus leaf extract, and chitosan against P. aeruginosa. The nanocomposite was synthesized using a green synthesis method, with plant extract serving as a natural reducing agent and chitosan as a nanoparticle stabilizer. Antibacterial activity was assessed via disk diffusion against five concentrations (6.25, 12.5, 15, 25, and 50 mg/mL), and compared to positive (chlorhexidine) and negative (acetic acid) controls. The results showed that the 6.25 mg/mL concentration produced the largest inhibition zone (average 11 mm), although it did not surpass the effectiveness of chlorhexidine. The inhibition zones remained stable for up to 72 hours, indicating sustained antibacterial activity. A decline in efficacy at 50 mg/mL was observed, likely due to nanoparticle aggregation and biological saturation. These findings support the potential of AgNO₃–C. citratus–chitosan nanocomposite as a natural-based alternative antibacterial agent. Further studies are recommended to characterize its physicochemical properties, elucidate its mechanism of action, and evaluate its toxicity and applicability in pharmaceutical and biomedical contexts.